2011
DOI: 10.1111/j.1365-246x.2011.05261.x
|View full text |Cite
|
Sign up to set email alerts
|

Remote triggering of non-volcanic tremor around Taiwan

Abstract: S U M M A R YWe perform a systematic survey of triggered deep 'non-volcanic' tremor beneath the Central Range (CR) in Taiwan for 45 teleseismic earthquakes from 1998 to 2009 with M w ≥ 7.5 and epicentral distance ≥1000 km to the broad-band station TPUB. Triggered tremors are visually identified as bursts of high-frequency (2-8 Hz), non-impulsive and long-duration seismic energy that are coherent among many seismic stations and modulated by the teleseismic surface waves. Out of the 45 earthquakes, we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
94
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(106 citation statements)
references
References 55 publications
(168 reference statements)
11
94
1
Order By: Relevance
“…This is consistent with similar findings in Cascadia (Ghosh et al, 2009(Ghosh et al, , 2010(Ghosh et al, , 2012, suggesting that array techniques have higher detection capabilities than traditional WECC techniques (Wech and Creager, 2008). Unfortunately, we did not have an existing fault interface model in this region (Chao et al, 2012), so we were unable to project the best slowness of tremor detection back to the source region to determine the tremor location, as was done in Cascadia and other regions (e.g., Ghosh et al, 2009).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This is consistent with similar findings in Cascadia (Ghosh et al, 2009(Ghosh et al, , 2010(Ghosh et al, , 2012, suggesting that array techniques have higher detection capabilities than traditional WECC techniques (Wech and Creager, 2008). Unfortunately, we did not have an existing fault interface model in this region (Chao et al, 2012), so we were unable to project the best slowness of tremor detection back to the source region to determine the tremor location, as was done in Cascadia and other regions (e.g., Ghosh et al, 2009).…”
Section: Discussionsupporting
confidence: 84%
“…In the arc-continent collision environment in Taiwan, tremor is found mainly beneath the southern Central Range (Peng and Chao, 2008;Tang et al, 2010Tang et al, , 2013Chao et al, 2011Chao et al, , 2012Chao et al, , 2013Chuang et al, 2014;Idehara et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gomberg (2010) further examined the relationship between the amplitudes of the triggering waves and triggered tremor from four observations in Cascadia (Rubinstein et al, 2009) and found that the results did not match the predictions of the clock-advance model. Chao, Peng, Wu, et al (2012) found a positive relationship between the amplitudes of surface waves from nine teleseismic earthquakes and those of triggered tremor beneath the Central Range in Taiwan. In addition, Chao, Peng, Fabian, et al (2012) compared triggered tremor observed in the Parkfield-Cholame section of the SAF with the San Jacinto fault (SJF) in southern California and the Calaveras fault (CF) in northern California.…”
Section: Introductionmentioning
confidence: 92%
“…The analysis procedure generally follows that of previous studies (Peng et al, 2009;Chao, Peng, Wu, et al, 2012) and is briefly described here. We download three-component broadband and short-period seismograms in each region (see Data and Resources), select the data from 1000 s before and 9000 s after the origin time of the Tohoku mainshock, remove the mean of the signals, and generate either band-pass (2-8 Hz) or high-pass (> 5 Hz) filtered seismograms.…”
Section: Data and Analysis Proceduresmentioning
confidence: 99%